Metode Fuzzy Untuk Mengidentifikasi Kepribadian Siswa - Amir Salim Khairul Rijal; Billy Hendrik (Universitas Maritim AMNI Semarang, 2023)
Personality recognition is one of the important things for recognizing oneself and other people. This identification is made based on a person's personality traits, based on Kant's personality theory. There are very few teachers who do not understand their students' personalities. During the teaching and learning process, some teachers do not clearly understand students' personalities, so it will be difficult for teachers to deliver learning material that arouses students' interest and thus influences the process of imparting knowledge. Consciousness is inhibited. Therefore, the FuzzyTsukamoto method is used to identify student personalities. The aim of this research is to help teachers group and identify students' personalities so that they can easily determine the right treatment method to develop their talents and interests. The system's input is taken from personality traits relevant to the student. The knowledge base is taken from child clinical psychologists and is built on the principle (IF-THEN). The results of the fuzzy calculation are that the student has a personality that is optimistic, quick-tempered, melancholic, or boring. The results of this method test by carrying out systematic calculations and tests, obtain personality results that are in accordance with the student's personality characteristics. and works fine. Therefore, it may be advisable to help teachers determine how to treat students.